Hubungan Paparan Foundation Dengan Timbulnya Akne Vulgaris Pada Siswi SMK Negeri 4 Surakarta - MARDIANA, MARDIANA, Dr. Flora Ramona S.P, M.Kes, Sp.K.K (2017)
Background : Acne vulgaris (AV) is a common skin disorder that affects at least 85% adolescent and young adult. The occurrence can be caused by various factors, including cosmetics. Foundation is a cosmetic that can cause acne vulgaris. Lanolin, preservative agent, and cetyl alcohol contained in foundation are acnegenic and comedogenic. These ingredients caused hyperkeratinization from pilosebaceous duct and increase the production of sebum on the face which caused development of acne vulgaris. Purpose : The purpose of this study is to discover the relationship between foundation exposure and acne vulgaris development. Methods : This research is was observational analytic with cross sectional approach. For significance test relationship between variable, using contingency coeffisien data analysis. instrumental is questionnaire and physical examination by general practitioners. Result : Based on 25 respondents that use foundation, 42,0% have acne vulgaris. Contingency coefficient test result for the relationship between foundation exposure and acne vulgaris development, with p value is less than p< 0,000 (p<0,05). Conclusion : There is a significant relationship between foundation exposure and acne development Keywords : Acne vulgaris, foundation, cosmetics